OCCUPATIONAL HEALTH AND SAFETY MANAGEMENT, EMPLOYEE ENGAGEMENT, AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR OF CLEANING WORKERS IN JAKARTA - Maryam, Suryani (KOMITMEN: Jurnal Ilmiah Manajemen, 2023)
The purpose of this research is to empirically test the effects of occupational health and safety management (OHS) and employee engagement associated with organizational citizenship behaviors (OCB). The study was conducted with 610 sewer cleaners in Jakarta Province and West Java Province-Indonesia using a survey instrument. Data analysis was done by Structural Equation Model (SEM). Three hypotheses were developed in order to determine the relationships between OHS management, employee engagement, and organizational citizenship behavior. The result of this study indicates that OHS management had a significantly positive impact on employees’ engagement and organizational citizenship behavior. This study makes several contributions to employers that by developing a systematic and integrated OHS management at the workplace, it can increase employee engagement and organizational citizenship behavior.